Electron-irradiation induced defects in Yb2Ti2.05O7. (15th January 2018) - Mostaed, Ali; Balakrishnan, Geetha; Lees, Martin R.; Beanland, Richard
Abstract: We present a scanning transmission electron microscopy (STEM) analysis of electron irradiation-induced defects in Yb2 Ti2 O7, which form in material with a deliberate Ti excess. No defects were observed to form in stoichiometric or Yb-rich material. The defects in the Ti rich materials are regions of lower density, roughly 1.5 nm in thickness, lying along { 111 } or { 110 } planes. A minority of defects also contain extrinsic partial dislocation loops. We use geometric phase analysis of atomically-resolved annular-dark field STEM images combined with dislocation tensor analysis in a new program BurgersVectors to show that the Burgers vector of the partial dislocations are of 1 / 4 〈 110 〉 type. Atomically-resolved energy-dispersive X-ray analysis shows that, although some cation disorder is observed in the affected region, the material does not fully transition to a defect fluorite structure. It is proposed that these phenomena, and their absence in stoichiometric and Yb-rich material, can be explained by the presence of negatively-charged Yb vacancies that are only present in material with a Ti excess. The injection of oxygen Frenkel pairs under energetic electron irradiation provides oxygen interstitials that can neutralize positively charged Ti atoms on the Yb sites, while the mobile oxygen vacancies combine with Yb vacancies and condense to form the observed low-density regions. Graphical abstract: Image 1